Relational connection and separation in Iranian dissertation defences - Don, Z.M.; Izadi, A. (Elsevier, 2010)
This article examines ways in which participants achieve face in Iranian dissertation defences, while doing interactional work in their roles as candidate, examiner or supervisor. Following Arundale, we adopt the notion of face as an interactional and relational phenomenon which is conjointly co-constituted by participants as they conjointly co-constitute meanings and actions in talk-in-interaction. This dynamic conceptualization of face requires an approach grounded in Conversational Analysis. The data for analysis is taken from two PhD defence sessions conducted at Iranian universities. Selected segments of talk from the Question and Answer sessions during these dissertation defences were analyzed to investigate how participants achieve face. The data analysis shows that interpreting and doing relational work are not only influenced by the participants' culture but also by the institutional nature of the talk itself. When covert rules are flouted, the reaction from co-participants and the audience demonstrates disapproval of inappropriate behaviour. (C) 2011 Elsevier B.V. All rights reserved.